Assisted convective heat transfer and entropy generation in a solar collector filled with nanofluid - Nasrin, R.; Alim, M.A.; Hasanuzzzaman, M. (Journal of Naval Architecture and Marine Engineering, 2016)
Heat transfer phenomena of flat plate solar collector filled with different nanofluids has been investigated numerically. Galerkins Finite Element Method is used to solve the problem. Heat transfer rate, average bulk temperature, average sub-domain velocity, outlet temperature, thermal efficiency, mean entropy generation and Bejan number has been investigated by varying the solid nanoparticle volume fraction of water/Cu, water/Ag and water/Cu/Ag nanofluids from 0% to 3%. It is found that the solid nanoparticle volume fraction has great effect on heat transfer phenomena. It is observed that the increases of the solid volume fraction (up to 2%) enhances the heat transfer rate and collector efficiency where after 2% the rate of change almost constant. Higher heat transfer rate and collector efficiency has been obtained 19% and 13% for water/Ag nanofluid respectively.